System integration for robotic surgical tool handling workcell - Chua, Chee Yung (Nanyang Technological University, 2022)
The rising trend of robot-assisted automation in the medical field has manifested great potential for development and deployment in substituting more repetitive tasks of human beings in hospitals. To cope with the limited healthcare service workforce and the overwhelming number of patients during the pandemic, technological means have been explored to enhance the operation from surgery rooms to wards of hospitals. A robotics surgical tools handling work cell is thus put forth to facilitate the inspection and replacement process on the instruments after being used in surgery. The development of such a handling system is multi-faceted and most of the previous research revolve around non-cognitive aspects rather than intensive intelligence-required regions like the inspection system. Under the collaboration with professional nurses of Singapore General Hospital (SGH), this project has demonstrated a permissible surgical tools handling approach by utilizing a 6 degrees of freedom robotics arm in a way that will not trigger any magnetization effect which would lead to severe incidence during life-saving operations. Furthermore, the project shows how Artificial Intelligence (AI) and Robotics Operating System (ROS) were employed in designing the entire system architecture and fulfilling the process flow requirements over multiple computers. The proposed system also incorporated a stereo camera and router to enhance the vision-aided system, enabling the system to capture Point Cloud data or perform image processing, along with the high-speed data transmission among the modules. Overall, the project has proven the concept to develop an automated robotics system in the surgical tools inspection and replacement process.